Optic neuritis - Katelytė , J.; Liutkevičienė , R. (Neurologijos seminarai, 2019)
Optic neuritis (ON) is a quite common condition and most neurologists are familiar with it. However, some studies show that at least 10% of cases are overdiagnosed. The most common mistake of diagnosing ON is wrong terminology and other illnesses which can mimic it. In this article, we discuss about typical “idiopathic” demyelinating optic neuropathy (IDON), its symptoms, diagnostic approaches, and diseases which can mimic IDON, including neuromyelitis optica, sarcoidosis, chronic relapsing inflammatory optic neuropathy, anterior ischemic optic neuropathy, neuroretinitis, Leber’s hereditary optic neuropathy, and some “ocular” mimics.
Keywords: optic neuritis; IDON; multiple sclerosis